H‐Dimeric Nanospheres of Amphipathic Squaraine Dye with an 81.2% Photothermal Conversion Efficiency for Photothermal Therapy. (16th March 2022) - Wang, Yigang; Xia, Guomin; Tan, Manman; Wang, Mingda; Li, Yingzhong; Wang, Hongming
Abstract: Understanding and implementing the ordered supramolecular assembly in organic photothermal materials is challenging, yet significant, for photothermal performance enhancement. Herein, an amphipathic squaraine dye (PSQ) with a poly (ethylene glycol) chain attached as a hydrophilic anchor is synthesized. In aqueous solution, PSQ spontaneously self‐assembles into uniform nanospheres (PSQ‐NSs) with well‐defined H‐dimeric substructures. Molecular dynamics simulations are conducted to illustrate the self‐assembly process. Reorganization energy calculations show that nonradiative decay is accelerated by H‐dimeric PSQ low‐frequency out‐of‐plane vibrational modes, which enables a rapid dissipation of excited‐state energy to heat. As such, the resultant H‐dimeric PSQ‐NSs exhibit ultrahigh photothermal conversion efficiency (81.2%) under laser irradiation (0.3 W cm −2, 808 nm) in water. In vitro and in vivo evaluations confirm their high stability, biocompatibility, tumor accumulation, and efficient tumor inhibition in photothermal therapy. It is expected that the self‐assembling H‐dimers will become a unique platform for the precise designing of small‐molecule PTAs for future clinical PTT applications. Abstract : A photothermal agent (PTA) based on an amphipathic squaraine dye is developed with high photothermal conversion efficiency (PCE, 81.2%). Implementing the strategy of H‐aggregation influences nonradiative decay process acceleration, promoting heat generation. In vitro and in vivo investigations confirm its high stability, biocompatibility, tumor accumulation, and efficient tumor ablation in photothermal therapy.